2017
DOI: 10.11621/pir.2017.0409
|View full text |Cite
|
Sign up to set email alerts
|

Big Five Factors and academic achievement in Russian students

Abstract: Background: The Five-Factor Model (FFM) of personality traits is one of the most comprehensive personality models in modern psychology. The traits, or domains, of the model, provide an extensive framework, which allows researchers to analyse the correlation between the aspects of personality and various aspects of social behaviour. Academic achievement is a key factor in a subject's success, and a more comprehensive understanding of its potential factors could improve educational programs and teaching strategi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0
14

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 37 publications
2
19
0
14
Order By: Relevance
“…The resulting values for each of the five personality factors (neuroticism, extraversion, openness, conscientiousness, and agreeableness) range from 12 to 60 points [44]. This version of the questionnaire has been well tested on different Russian samples [19,21,45].…”
Section: Techniquesmentioning
confidence: 99%
See 4 more Smart Citations
“…The resulting values for each of the five personality factors (neuroticism, extraversion, openness, conscientiousness, and agreeableness) range from 12 to 60 points [44]. This version of the questionnaire has been well tested on different Russian samples [19,21,45].…”
Section: Techniquesmentioning
confidence: 99%
“…Numerous studies show that openness to experience and especially conscientiousness are significant predictors of academic achievements for most studied subjects, including FL/SL [15][16][17]. Recent Russian research based on the FFM has shown that conscientiousness impacts the academic achievements of Russian university and grade-school students [18][19][20][21]. However, a study of Russian linguistics students' academic achievements in different subjects showed that none of the FFM traits are associated with a student's final grades in English (as the "first" and mandatory FL), while conscientiousness, extraversion, and neuroticism are correlated with the final grades for their "second" elective FL [18].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations